SYNTHESIS AND CHARACTERIZATION OF NOVEL SA-PA-LSA/C-30B/AG NANOCOMPOSITES FOR SWELLING, ANTIBACTERIAL, DRUG DELIVERY, AND ANTICANCER APPLICATIONS - BH, Nanjunda Reddy; RANJAN RAUTA, PRADIPTA; V, Venkatalakshimi; Sreenivasa, Swamy (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Â Objective: The main objective of this work was to formulate and evaluate Closite-30B/nanoAg filled hydrogel composites which are further intentended to be used for the study of drug delivery,antibacterial, and anticancer activity Methods: In this study, Cloisite-30B (C-30B) clay dispersed biopolymer sodium alginate (SA)-grafted-poly (acrylamide [AAm]-co-lignosulfonic acid) hydrogel composites were synthesized by free radical in situ polymerization reaction technique using SA, AAm, and lignosulfonic acid biopolymers in different proportions in combination. which are subjected to invitro drug delivery and Minimum inhibitory concentration(MIC) method for antibacterial activity study by using Streptococcus faecalis (S.faecalis) and Escherichia coli (E. coli)bacteria. The biocompatibility of the prepared gels were determined by standard protocol HaCaT-cells and MCF-7 cell lines further the prepared hydrogel composites were characterized for particle size,encapsulation efficiency,swelling properties,compatibility studies by FTIR etc. Results: The formulated hydrogels were characterized by X-ray diffraction (XRD) to analyze the particles size and crystallinity. The presence of functional groups and their chemical interaction with the drug, C-30B, and silver nanoparticles (AgNPs) were confirmed by the FTIR spectroscopy. Furthermore, the presence of AgNPs in the matrix was confirmed by ultraviolet/visible spectroscopy. Thermogravimetric analysis was performed to find out the thermal degradation, thermal stability, and the percentage of weight loss at various temperatures. Swelling studies revealed that C-30B and AgNPs induced composites exhibited higher swelling ratio than pure hydrogels. The hydrogels with C-30B/AgNPs displayed excellent antibacterial activity against both Gram-positive and Gram-negative bacteria. Further, these hydrogel composites were loaded with the drug paclitaxel (PT), and drug release study showed that the sustained release of the drug from C-30B/Ag hydrogel matrix compared to rest of other samples. Hydrogel composites were cytocompatible in nature (with HaCaT cells) and the cell viability decreased (with MCF-7cells) with the presence of lignosulfonic acid as well as C-30B and AgNPs in the samples as evaluated through 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyl tetrazolium bromide to its insoluble formazan assay. Conclusion: The synthesized hydrogel composites were successfully characterized and eavaluated for sustained release of paclitaxel drug delivery at different pHs and temperatures and it is found that C30B/Ag filled composites exhibits contolled release of drug with higher rate, especially at lower pH (pH2) and higher temperature (37oC) and the same formulations which exhibits better anitbcterial and anticancer activity compared to the virgin samples So the prepared C30B/AgNPs hydrogels composites used in drug dlivery for the effective treatment of cancer and used against bacterias and cancerous cells.